2015
DOI: 10.1021/acsphotonics.5b00351
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Radiation Imaging of Ferroelectric Domain Topography in Room-Temperature Hydrogen-Bonded Supramolecular Ferroelectrics

Abstract: Organic ferroelectrics with lightweight, flexible, low-cost, and environmentally benign characteristics are recently receiving great attention for new electric and optical devices. Since the propagation of ferroelectric domain walls and the subsequent reformation of ferroelectric domains are the basis for these devices, detection of the ferroelectric domain topology is crucial. Here, we demonstrate a new method to detect ferroelectric domains in inside and surface regions of organic ferroelectrics by mapping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
(151 reference statements)
2
7
0
Order By: Relevance
“…Unless otherwise stated, we detected the emitted terahertz wave by a standard electro-optic (EO) sampling with an [110]-oriented 1mm-thick ZnTe crystal. By using terahertz radiation imaging[22][23][24][25][26], we confirmed that the BiTeBr crystal used in the present study has a polar single-domain structure. The result of the domain imaging is reported in the Supplemental Material[27].…”
supporting
confidence: 77%
“…Unless otherwise stated, we detected the emitted terahertz wave by a standard electro-optic (EO) sampling with an [110]-oriented 1mm-thick ZnTe crystal. By using terahertz radiation imaging[22][23][24][25][26], we confirmed that the BiTeBr crystal used in the present study has a polar single-domain structure. The result of the domain imaging is reported in the Supplemental Material[27].…”
supporting
confidence: 77%
“…Comparing the two types of extensions, the one-dimensional extension seems to be more easily realized. Such tendency is also found in the microscope images of ferroelectric domains in the croconic acid crystal [28] and other materials [35,36], as a prevalence of one-dimensional domains, that are, line-or stripe-type domains running along the polarization direction. We also estimate a maximum domain size for the case of the one-dimensional domain as follows.…”
mentioning
confidence: 58%
“…Laser-excited THz microscopy (LTEM) has also introduced THz pulses to various scientific and industrial fields. THz-TDS measures the optical properties of materials, whereas LTEM evaluates the dynamics of carriers or electric dipoles in materials and has already analyzed high-temperature superconductors (HTS) [8,9], ferroelectrics [10] and semiconductor devices [11][12][13][14]. LTEM irradiates materials by femtosecond laser pulses, generating THz radiation.…”
Section: Introductionmentioning
confidence: 99%